Competition law and policy in Japan and the EU - Kameoka, Etsuko (Cheltenham, UK : Edward Elgar, 2014)
This exciting new book embarks on a comparative analysis of competition law and policy in Japan and the EU. It provides a clear and carefully researched exposition of the differences between the relevant rules, systems and underlying ideas of the two jurisdictions, together with the relevant historical backgrounds. The author chooses to discuss the main areas of competition law in these jurisdictions, with particular focus placed on the gaps between the written law and practice, including analysis of the current debates that suggest future directions in competition and policy will aim towards harmonization of both systems. Competition Law and Policy in Japan and EU will strongly appeal to academics, researchers, public enforcers, practitioners, in-house counsel and students.
Historical background -- Legal structure and enforcement -- Cartels and bid rigging -- Vertical restraints -- Abuse of dominance -- Merger control -- Procedure -- Fining policy -- IP and competition -- Private enforcement -- International aspects of competition law enforcement.
Includes bibliographical references (pages 202-204) and index.
Keywords: Antitrust law -- Japan; Antitrust law -- European Union countries